Volume 1: Advances in Control Design Methods, Nonlinear and Optimal Control, Robotics, and Wind Energy Systems; Aerospace Appli 2016
DOI: 10.1115/dscc2016-9828
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Muscular Nonfatigue and Fatigue Conditions Using Surface EMG Signals and Fractal Algorithms

Abstract: The application of surface electromyography (sEMG) technique for muscle fatigue studies is gaining importance in the field of clinical rehabilitation and sports medicine. These sEMG signals are highly nonstationary and exhibit scale-invariant self-similarity structure. The fractal analysis can estimate the scale invariance in the form of fractal dimension (FD) using monofractal (global single FD) or multifractal (local varying FD) algorithms. A comprehensive study of sEMG signal for muscle fatigue using both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Concerning chaos, correlation, entropy, and fractals MMF indicators, Higuchi fractal dimension and fuzzy entropy were the only indicators that had high VIP values (1.26-2.03) and changed significantly for a large proportion of the participants (65%-90%) for the anterior and medial deltoids. Higuchi fractal dimension therefore confirms that the fractal dimension is sensitive to intrinsic changes of EMG signals occurring with muscle fatigue [18,49]. As to fuzzy entropy, our results are in line with Xie et al, [54] which stated that it provides an improved evaluation of time series complexity.…”
Section: Mmf Indicators To Assess Muscle Fatiguesupporting
confidence: 89%
See 2 more Smart Citations
“…Concerning chaos, correlation, entropy, and fractals MMF indicators, Higuchi fractal dimension and fuzzy entropy were the only indicators that had high VIP values (1.26-2.03) and changed significantly for a large proportion of the participants (65%-90%) for the anterior and medial deltoids. Higuchi fractal dimension therefore confirms that the fractal dimension is sensitive to intrinsic changes of EMG signals occurring with muscle fatigue [18,49]. As to fuzzy entropy, our results are in line with Xie et al, [54] which stated that it provides an improved evaluation of time series complexity.…”
Section: Mmf Indicators To Assess Muscle Fatiguesupporting
confidence: 89%
“…In a recent study, Ni et al, [68] showed that time, frequency, and time- Consequently, the aim of the present study was to determine the best MMF indicators, f rom 15 MMF indicators identified in the literature as potentially relevant to assess muscle fatigue during a repetitive pointing task (RPT) performed with the upper limb. We hypothesized that for the anterior and medial deltoids, which are the muscles showing the largest signs of fatigue during the upper limb repetitive task used in the present studies [72][73][74], the mobility, median frequency, spectral entropy, fuzzy entropy, multiscale entropy [24,28,41,75,76], and degree of multifractality [40,47,49,53] will have greater importance to predict the evolution of the RPE. In addition, these MMF indicators will significantly change for a large proportion of the participants in the anterior and medial deltoid in comparison to approximate and sample entropy, recurrence quantification analysis, correlation dimension, and the largest Lyapunov exponent [28,40,46,55].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FD methods for assessing muscle fatigue have increased in importance over the last 10 years, with researchers using different methods, such as the box-counting method ( Troiano et al, 2008 , Beretta-Piccoli et al, 2015 ; Boccia et al, 2016 ) to understand the fractal behavior. Marri and Swaminathan (2016) used several methods [e.g., Higuchi (1988) , Katz, Sevcik, box counting; multifractal analysis]. In most cases, Marri and Swaminathan’s (2016) monofractal algorithms delivered smaller FDs for fatigued muscles compared to non-fatigue; while the opposite was true for multifractal algorithms where the FD was mostly smaller than 1.…”
Section: Introductionmentioning
confidence: 99%
“… Marri and Swaminathan (2016) used several methods [e.g., Higuchi (1988) , Katz, Sevcik, box counting; multifractal analysis]. In most cases, Marri and Swaminathan’s (2016) monofractal algorithms delivered smaller FDs for fatigued muscles compared to non-fatigue; while the opposite was true for multifractal algorithms where the FD was mostly smaller than 1. In general, a signal’s FD ranges between a value of 1 and 2, i.e., between a straight line or smooth curve, and a maximally noisy signal filling up an area ( Fuss, 2013 ).…”
Section: Introductionmentioning
confidence: 99%